2008
DOI: 10.1021/ef800417v
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Natural Sorbents for Removing CO2 from Combustion Gases, as Studied in a Bench-Scale Fluidized Bed

Abstract: The reaction of CO 2 with porous particles of CaO in CaO (cr) + CO 2(g) f CaCO 3(cr) was studied, along with its reverse reaction, for chicken eggshells, mussel shells, and limestone. Reaction I is a promising way of removing CO 2 , e.g., from the exhaust of a power station, so that a pure stream of CO 2 can subsequently be produced for sequestration by calcining (roasting) the solid CaCO 3 from reaction I. The reverse of reaction I regenerates the sorbent, which can thus be used cyclically. The forward and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…These properties depend on impurities and the conditions / age of formation. Dolomites have shown a reduced decay rate upon cycling, despite a lower initial reactivity owing to a lower amount of CaO per unit mass (Dobner et al, 1977;Silaban et al, 1996); natural sorbents such as shells have also been studied and have been shown to exhibit mildly increased reactivity in comparison to natural limestone in some cases (Ives et al, 2008;Li et al, 2009). Doping of natural limestones has been investigated; however the results have been variable (Salvador et al, 2003;Fennell et al, 2007b;Florin and Harris, 2008b;Sun et al, 2008), even when the same dopant has been used.…”
Section: Sorbent Performancementioning
confidence: 99%
“…These properties depend on impurities and the conditions / age of formation. Dolomites have shown a reduced decay rate upon cycling, despite a lower initial reactivity owing to a lower amount of CaO per unit mass (Dobner et al, 1977;Silaban et al, 1996); natural sorbents such as shells have also been studied and have been shown to exhibit mildly increased reactivity in comparison to natural limestone in some cases (Ives et al, 2008;Li et al, 2009). Doping of natural limestones has been investigated; however the results have been variable (Salvador et al, 2003;Fennell et al, 2007b;Florin and Harris, 2008b;Sun et al, 2008), even when the same dopant has been used.…”
Section: Sorbent Performancementioning
confidence: 99%
“…Second, there is vast experience in handling lime products, and any spent material from a lime-based process can, in principle, either be used or disposed of relatively easily. 10,19 Grasa and Abanades 20 carried out an extended series of trials and found that there is a residual carrying capacity remaining aft er 500 cycles. 17 Yong et al 18 represent the ideal properties of a sorbent in terms of fi ve distinct characteristics (Fig.…”
Section: Use Of Lime-based Sorbents For Co 2 Removalmentioning
confidence: 99%
“…Since the eggshells of chicken and quail are composed of calcium carbonates, their calcination at above 700°C produces basic calcium oxide which can be used as a basic adsorbent for carbon dioxide (Ives et al, 2008) and as a catalyst for the production of biodiesel (Wei et al, 2009). These eggshells are composed of three layers: a thin cuticle outer layer, a thick palisade middle layer and a thin mammillary inner layer.…”
Section: Introductionmentioning
confidence: 99%